2015
DOI: 10.1136/bmjdrc-2015-000129
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of visit-to-visit variability in HbA1c and systolic blood pressure on the incidence of cardiovascular events in patients with type 2 diabetes

Abstract: ObjectiveTo investigate the association between long-term visit-to-visit variability in glycated hemoglobin (HbA1c) and systolic blood pressure (SBP) and the incidence of cardiovascular disease (CVD) in patients with type 2 diabetes.MethodsWe retrospectively enrolled 632 patients with type 2 diabetes and no history of CVD who first visited our hospital between 1995 and 1996, were followed-up for ≥1 year, attended at least 4 clinic visits and had at least 1 visit per year. Patients were followed until June 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 30 publications
1
30
1
Order By: Relevance
“…and blood lipids of males in this age-group have worse control conditions, and women may be easily affected by physiological cycle. As in previous reports (19,(22)(23)(24), gender differences were noted in the relationship between HbA1c and age. It is possible that this finding is related to lower hemoglobin levels in menstruating women with more rapid erythrocyte turnover, as suggested previously (19).…”
Section: Discussionsupporting
confidence: 56%
“…and blood lipids of males in this age-group have worse control conditions, and women may be easily affected by physiological cycle. As in previous reports (19,(22)(23)(24), gender differences were noted in the relationship between HbA1c and age. It is possible that this finding is related to lower hemoglobin levels in menstruating women with more rapid erythrocyte turnover, as suggested previously (19).…”
Section: Discussionsupporting
confidence: 56%
“…Full‐text versions of the remaining 73 articles were retrieved and singularly examined. Ultimately, 47 studies were excluded and, of the remaining 26 papers that were included, 22 were selected for quantitative analysis . Secondary endpoints (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that HbA1c variability was a predictor of CVD incidence and all‐cause mortality in type 2 diabetes patients independent of mean HbA1c level. Thus, these adverse events might be influenced by both short‐term glucose excursions and long‐term glycemic variability in type 2 diabetes patients.…”
Section: Discussionmentioning
confidence: 96%